2017
DOI: 10.22456/1679-9216.80769
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Three Acepromazine Doses on the Incidence of Morphine-Induced Vomiting, Sedation and Some Physiological Variables in Dogs

Abstract: Background: Acepromazine was found to reduce the incidence of vomiting induced by opioids such as morphine, hydromorphone and oxymorphone in dogs. Despite the effectiveness of the phenothiazine in preventing opioid-induced vomiting in this species, a single dose of acepromazine (0.05 mg/kg) was tested and the influence of dose on the antiemetic effect of the drug is unknown. The primary objective of this study was to evaluate the effect of three acepromazine doses on the incidence of vomiting induced by morphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…A recent Cochrane review found no evidence that droperidol caused more cardiovascular arrhythmia than placebo with short-term use. 68 In animal studies, the influence of acepromazine on morphine's cardiovascular effects was not consistent in the study of Monteiro et al 43 when heart rate and arterial pressure were measured using an oscillometric device with the cuff bladder placed above the dogs' carpus. Decreases in both pulse rate and mean arterial pressure were observed with morphine monotherapy and morphine-acepromazine but only compared to baseline and not between the different acepromazine groups or morphine monotherapy.…”
Section: Cardiovascular Effectsmentioning
confidence: 96%
See 3 more Smart Citations
“…A recent Cochrane review found no evidence that droperidol caused more cardiovascular arrhythmia than placebo with short-term use. 68 In animal studies, the influence of acepromazine on morphine's cardiovascular effects was not consistent in the study of Monteiro et al 43 when heart rate and arterial pressure were measured using an oscillometric device with the cuff bladder placed above the dogs' carpus. Decreases in both pulse rate and mean arterial pressure were observed with morphine monotherapy and morphine-acepromazine but only compared to baseline and not between the different acepromazine groups or morphine monotherapy.…”
Section: Cardiovascular Effectsmentioning
confidence: 96%
“…Monteiro et al 43 found no change in the degree of sedation when morphine was combined with acepromazine compared to morphine monotherapy. However, the sedative effect was more rapidly obtained when acepromazine was co-administered.…”
Section: Sedative Effectsmentioning
confidence: 97%
See 2 more Smart Citations
“…Telemetry recordings were acquired continuously for 60 min before the first dose of intervention to obtain baseline values of the cardiovascular variables 20 . Recordings were run continuously during baseline and administration of increasing doses of the drugs or vehicle until 40 min after the last dose 21 . Afterwards, rats were anaesthetized with isoflurane and euthanized by exsanguination.…”
Section: Methodsmentioning
confidence: 99%